EKSPLORASI STRUKTUR GUNUNG ES (ICEBERG) PADA BUSANA PESTA SORE DENGAN TEKNIK RUFFLES - Shofura Azhar Nabila; Feny Puspitasari (Universitas Pendidikan Indonesia, 2017)
The iceberg (Iceberg) is a large chunk of freshwater ice that has been split from glaciers or ice shelf and floating open water. Since density (density) of ice is lower than sea water, generally 90% of the volume of icebergs is below sea level. Ruffle is a wrinkled or pleated cloth wider than the frills generating floating waves attached to the fabric that produces dimensions and waves on the decorated part also can be combined with many piles and cut in various ways and sizes, including ruffle into fabric manipulation techniques. Because of the uniqueness of the iceberg form the authors are inspired to apply the form of an iceberg characterized by a smaller volume above the sea surface ie the peak and the greater volume of iceberg beneath the surface of the sea against the exploration of party fashions with ruffle techniques. The purpose of designing fashion products at this fashion seminar is to meet one of the tasks of seminars education education courses and also has experience in applying the beauty of the iceberg threatened to melt because of the earth warming of party dress with ruffle techniques. The method used is a project based learning consisting of several stages, including finding sources of ideas, searching the literature, and conducting experiments that began from the making of moodboard, fashion design, and the manufacture of fashion products. The expected findings of this design are the successful application of icebergs to the exploration of party fashions with ruffle techniques.